Diprotin A TFA Exerts Neurovascular Protection in Ischemic Cerebral Stroke - Zhou, Ming-Yue; Zhang, Ya-Jie; Ding, Hong-Mei; Wu, Wei-Feng; Cai, Wei-Wei; Wang, Yan-Qiang; Geng, De-Qin (Frontiers in Neuroscience, 2022)
Abstract Background: It has been established that the DPP-4 inhibitor Diprotin A TFA can reduce VE-cadherin disruption by inhibiting the increase in cleaved β-catenin in response to hypoxia, thereby protecting the vascular barrier of human umbilical vein endothelial cells. In the present study, we sought to investigate the possible effect of Diprotin A TFA on the vascular endothelial barrier after cerebral ischemic stroke in mice. Methods: C57BL/6 mice were divided into five groups: (1) sham; (2) stroke; (3) stroke + DMSO; (4) stroke + Diprotin A TFA; and (5) stroke + Diprotin A TFA + XAV-939. First, the cerebral ischemia model was established by photothrombotic ischemia, followed by intraperitoneal injection with Diprotin A TFA and XAV-939 at doses of 70 μg/kg and 40 mg/kg 30 min once in the morning and once in the evening for 3 days. Immunofluorescence staining and western blot methods were used to analyze the expression of vascular and blood-brain barrier-associated molecular markers in the peri-infarct area. Results: Compared with the vehicle control group, we found that mice injected with Diprotin A TFA exhibited reduced cerebral infarction volume, increased vascular area and length around the brain injury, increased pericyte and basement membrane coverage, up-regulated expression of blood-brain barrier (BBB) tight junction proteins, and improved their BBB permeability; while the group injected with both drug and inhibitor exhibited significantly aggravated vascular injury and BBB permeability. Conclusion: Diprotin A TFA can reduce VE-cadherin disruption by inhibiting ischemia-hypoxia-induced β-catenin cleavage to, protect blood vessels.